Open access for gamification: a systematic review of literature across disciplines - Zakaria, Noor Syamilah; Saripan, M. Iqbal; Subarimaniam, Neerushah; Ismail, Alyani (Innovare Academics Sciences, 2020)
Gamification is a combination of mission, story, and desirable behaviors that increases the likelihood of people showing particular behaviors. With the increasing need for developing effective learning methods, gamification has been widely used as a tool to improve the desire and interest in learning. The objective of this review is to identify disciplines, purposes, and target users of gamification through a systematic review involving gamification-related ‘open access’ scholarly materials. Using a series of rule performed through the Scopus database, we have examined 14 articles for an extensive review. We found that gamification fits numerous purposes and fields, allowing developers to expand their algorithms to be used for various subjects in different settings. Education leads the process of facilitating gamification and thus, we conclude that gamification is an attractive multidisciplinary learning tool. This review permits the implementation of gamification in many other disciplines and subsequently, increase desired behaviors.